Indicators of Obesity and Cardiorespiratory Fitness in Croatian Children - Marko Badrić; Leona Roca; Vladan Pelemiš; Dragan Branković; Vladimir Živanović (Journal of Functional Morphology and Kinesiology)
Background/Objectives: The aim of this study is to investigate the relationship between CRF (cardiorespiratory fitness) and body composition, specifically obesity indicators, in a sample of schoolchildren from the continental and Adriatic regions of the Republic of Croatia. Given that Croatia ranks among the leading countries in Europe in terms of obesity, it is believed that there is a need to combat this condition starting from school age. The usefulness of cardiorespiratory fitness (CRF) lies in the fact that it is one of the indicators of children’s overall health and is considered a measure of general health status. The findings will emphasize the need to determine CRF and BMI as important factors that should be addressed from early school years in order to prevent future cardiovascular diseases. Methods: The total sample consisted of 423 students, including 212 girls and 211 boys, from the continental and Adriatic regions of the Republic of Croatia, with an average age of 10.32 years. Body height was measured using a portable stadiometer, while body weight, body mass index (BMI), and body fat percentage were measured using a dual-frequency body composition analyzer (TANITA DC-360P) based on the principles of bioelectrical impedance. The WHR index was calculated as the ratio of waist to hips, while the WHtR index was calculated as the ratio of waist circumference to height. Cardiorespiratory fitness was assessed using the 20-meter multistage shuttle run test. Results: The results show that 25% of the participants were overweight, and 9% were obese. The ANOVA results indicate that the boys had significantly higher values for BMI, WC, HC, WHtR, and WHR, while the girls had a significantly higher body fat percentage (BF%). Additionally, the boys had better CRF, as they ran more meters in the 20-meter shuttle run test. The variance analysis revealed that the participants with normal body weight had significantly higher cardiorespiratory capacity values compared to overweight or obese students. Regression analysis showed statistical significance for the set of predictor variables, which were BMI indicators, on the criterion variable predicting cardiorespiratory fitness (CRF) in both genders. The coefficient of determination (R2) explained almost 22% of the shared variability in boys and 19% in girls. Statistically significant beta coefficients were found for body fat percentage (−0.60) in boys and (−0.98) in girls. Conclusions: Body fat percentage (BF%) was shown to be a significant and useful predictor of cardiorespiratory fitness in school-aged boys and girls. Maintaining an optimal body weight along with high levels of CRF should be an important goal in promoting health among children and adolescents.